23 Cytomorphological Patterns of Malignant Lymph Nodes in a tertiary Care Centre - Aishvarya Jandial; Subhash Bhardwaj; Akhil Mahajan (Dr. Annil Mahajan, 2022)
Background: The lymph nodes function as an antigen filter for the reticuloendothelial system. They form part of immune system and function to fight disease and infections. Thus, clinical recognition and urgent diagnosis of palpable lymphadenopathy is of paramount importance. The aim of this study was to analyse the cytomorphological patterns of malignant lymph nodes by using FNAC. Material and Methods: This is an observational study which includes fine needle aspiration cytology of 160 cases of lymphadenopathy presenting to the department of pathology for 2 years. Results: A total of 160 malignant lymph node lesions were aspirated, of which 127 (79.38%) were of metastatic origin and 33 (20.63%) were reported as lymphomas. The most common metastatic malignancy reported was squamous cell carcinoma (62.98%). The cervical lymph node was the most commonly involved lymph node. Conclusion: The head and neck was reported as the most common primary site in case of metastatic squamous cell carcinoma. FNAC is an effective, reliable and safe diagnostic modality for the diagnosis of malignant lymph node lesions.